(untitled) (Research, Society and Development, 2022)
Hydraulic conductivity (Kθ) is an important attribute for soil physical quality assessment. The objective was to evaluate the Kθ of an Oxisol in different systems of use and management. A randomized block design with 10 treatments was used: single corn; organic corn; corn (organomineral); corn + biochar; cover plant mix; corn + brachiaria; corn + sunn hemp; mix of cover crops + biochar; millet and SPD: mix of cover crops (millet + sunn hemp + brachiaria) and 3 replications. Kθ was determined using a table permeameter. The samples were subjected to 30 mm water columns and the readings were recorded at 1 hour intervals, for at least 8 hours, or until stability was reached. The management systems do not affected the hydraulic conductivitiy of the soil dystrophic red-yellow Latosol in the layer from 0.00 to 0.10 m, affecting only the layer from 0.10 to 0.20 m. All soil use and management systems increase soil hydraulic conductivity in the 0.10 to 0.20 m layer, except for Corn + sunn hemp.